Emerging indications for hyperbaric oxygen. Issue 6 (December 2019) - Bennett, Michael H.; Mitchell, Simon J.
Abstract : Purpose of review: To identify and discuss emerging trends in the therapeutic use of hyperbaric oxygen. Recent findings: There has been a maturing of the clinical evidence to support the treatment of sudden hearing loss, a wide range of problematic chronic wound states and the prevention and treatment of end-organ damage associated with diabetes mellitus. On the other hand, the controversy continues concerning the use of hyperbaric oxygen therapy (HBOT) to treat sequelae of mild traumatic brain injury. HBOT remains poorly understood by many medical practitioners despite more than 50 years of clinical practice. Pharmacological actions arise from increased pressures of oxygen in the blood and tissues. Most therapeutic mechanisms identified are not the simple result of the reoxygenation of hypoxic tissue, but specific effects on immunological and metabolic pathways by this highly reactive element. HBOT remains controversial despite biological plausibility and a solid clinical evidence base in several disease states. Summary: Multiple proposals for new indications for HBOT continue to emerge. Although many of these will likely prove of limited clinical importance, some show significant promise. Responsible practitioners remain acutely aware of the need for high-quality clinical evidence before introducing emerging indications into routine practice.